2022
DOI: 10.3390/metabo12050405
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor Isoforms Alpha and Beta Play Convergent Roles in Muscle Physiology and Metabolic Regulation

Abstract: Skeletal muscle is a key energy-regulating organ, skilled in rapidly boosting the rate of energy production and substrate consumption following increased workload demand. The alteration of skeletal muscle metabolism is directly associated with numerous pathologies and disorders. Thyroid hormones (THs) and their receptors (TRs, namely, TRα and TRβ) exert pleiotropic functions in almost all cells and tissues. Skeletal muscle is a major THs-target tissue and alterations of THs levels have multiple influences on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…Considering the lower level of TRα observed in our study and its vital role in maintaining mitochondrial function according to previous studies [16,17], we hypothesized that aging related muscle loss might result from the loss of TRα.…”
Section: Decreased Expression Of Trα In Sm With Agingsupporting
confidence: 53%
See 1 more Smart Citation
“…Considering the lower level of TRα observed in our study and its vital role in maintaining mitochondrial function according to previous studies [16,17], we hypothesized that aging related muscle loss might result from the loss of TRα.…”
Section: Decreased Expression Of Trα In Sm With Agingsupporting
confidence: 53%
“…Mitochondrial dysfunction had intimate relationship with senescence and SM degeneration. TH signaling pathway has been proved to regulate mitochondrial quality control systems including mitochondrial dynamics and mitophagy, as well as mitochondrial function in SM [13][14][15][16][17]. However, the role of TRα in regulating mitochondrial quality control systems and mitochondrial function during aging is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…THs can also influence the levels of PA. Agitation is a characteristic of hyperthyroidism while hypothyroid patients tend to be less active [2]. TH receptors TRα and TRβ are both critical regulators of muscular genes and alterations in TRs are associated with muscle dysfunctions in mice and humans [31,32]. In a study in 2023, Miro et al have indicated that THs alter the proportion of saturated and unsaturated fatty acids (FAs) in Skeletal muscle (SKM) lipids membrane, and regulated the lipid content of muscle fibres, thereby affecting physical exercise performance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Central and local thyroid hormones dysfunctions are frequent conditions reported in case of ischemic events. THs are involved in several physiological processes and, in particular, are important players in driving the development and the maturation of multiple tissues through genomic and non-genomic actions [ 23 , 24 , 67 , 92 , 115 , 123 ]. It has long been known that THs have a variety of effects on the cardiovascular system and brain development.…”
Section: Discussionmentioning
confidence: 99%
“…The complex relationship between the thyroid hormones serum concentration and the insurgence, severity and recovery after stroke remains controversial because thyroid hormones exert both neurotoxic and neuroprotective effects [ 20 , 21 ]. Thyroid hormones (THs), the prohormone L-Thyroxine (T4, or 3,3′,5,5′-tetraiodo-L-thyronine) and the active form Triiodothyronine (T3, or 3,3′,5-triiodo-L-thyronine), are pivotal determinants of the energy metabolism and the homeostatic control of basically every body tissue [ 22 , 23 , 24 ]. While the systemic THs concentration depends on a central control exerted by the Hypothalamus-Pituitary-Thyroid (HPT) axis, their intracellular levels are finely tuned by a complex network of crucial regulators of THs signaling: the plasma membrane transporters, mainly MCT8 and MCT10, which mediate the THs cellular uptake [ 25 ]; the different isoforms of THs receptors, TRα and TRβ that, through the binding to THs, regulate the transcription of TH target genes [ 26 ], and the deiodinase enzymes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%